Conceitos e práticas de geodesign aplicados ao ordenamento territorial do município de São Gonçalo do Rio Abaixo - Braulio Magalhaes Fonseca (2015)
This thesis is divided into four chapters (each one corresponding to one paper) preceded by an introductory chapter and succeeded by two conclusion chapters. The research has a methodological nature, and was based on the Geodesign framework. As a concept, the term Geodesign presupposes the sustainable integration of human activities with the environment, respecting the cultural peculiarities and providing a decision-making process in a democratic way. As a practice, Geodesign is a systematic methodological framework of territorial planning supported by tools for modeling of environmental systems and new tools to be developed. The municipality of São Gonçalo do Rio Abaixo was selected as a pilot area due to the significant economic and environmental changes as a consequence of mining activity. In Chapter 2 (Paper 1), there have been applied concepts and techniques of Landscape Ecology with Geographic Information System (GIS) tools to evaluate vegetation fragments in urban areas. In Chapter 3 (Paper 2), there was evaluated the land use suitability from the perspective of geomorphologic factors. To this end, it was considered the synthesis of variables related to the slope processes expressed in the relief roughness, the morphological patterns grouped in geomorphologic units, geotechnical properties of rocks, grouped in geotechnical units, and hydrodynamic processes synthesized by the energy present in the drainage systems, calculated with Hack index (SL index). In Chapter 4 (Paper 3), there were evaluated processes that increase the urban expansion and environmental processes related to the need of environmental preservation. With this purpose, it was employed participatory multi-criteria analysis, adapting the Delphi method, which in this case was directed to expert professionals who are also social actors in the area of study. It was applied the uncertainty analysis (Monte Carlo Simulation) and sensitivity analysis (Variance Decomposition) to evaluate the consistency and robustness of the results. In Chapter 5 (Paper 4), it was structured a change model based on historical data and new approved urban projects in the study area. In order to analyze the changes, there have been used Landsat images and Land Change Modeler model (LCM-IDRISI). In this paper it was also presented an impact assessment model, combining the urban expansion modeling with the environmental suitability map (need of environmental preservation). The results have shown areas presenting conflict of interest, areas in balance and areas suitable for projects based on Geodesign. In general the results allowed the support of the hypothesis that the area of study is in relative balance, or on implicit geodesign condition, not presenting large areas with conflict of interest, resulting in a low overall potential of impacts related to the urban activities.